The use of photodynamic therapy in medical practice - Aebisher, David; Rogóż, Kacper; Myśliwiec, Angelika; Dynarowicz, Klaudia; Wiench, Rafał; Cieślar, Grzegorz; Kawczyk-Krupka, Aleksandra; Bartusik-Aebisher, Dorota (Frontiers in Oncology, 2024)
Cancer therapy, especially for tumors near sensitive areas, demands precise treatment. This review explores photodynamic therapy (PDT), a method leveraging photosensitizers (PS), specific wavelength light, and oxygen to target cancer effectively. Recent advancements affirm PDT’s efficacy, utilizing ROS generation to induce cancer cell death. With a history spanning over decades, PDT’s dynamic evolution has expanded its application across dermatology, oncology, and dentistry. This review aims to dissect PDT’s principles, from its inception to contemporary medical applications, highlighting its role in modern cancer treatment strategies.